Nitrogen and sulfur co-doped carbon material as well as preparation method and application thereof
By doping nitrogen and sulfur diatoms on the carbon precursor, the problem of insufficient stability of the existing platinum carbon catalyst is solved, and the oxygen reduction reaction activity and stability of the catalyst is improved, making it suitable for commercial applications of fuel cells.
Patent Information
- Application Number
- CN202311321127.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-15
AI Technical Summary
The existing platinum carbon catalysts have insufficient oxygen reduction electrocatalytic stability, which is difficult to meet the needs of large-scale commercial applications of fuel cells.
By doping nitrogen and sulfur diatoms on the carbon precursor with a pore structure, the doping content is reasonably regulated, ensuring the stability of the pore structure of the carbon support, and at the same time improving the oxygen reduction reaction activity and stability of the platinum carbon catalyst.
The ORR activity and stability of platinum carbon catalysts have been improved, the process has been simplified, the utilization rate of doping sources has been improved, and it is suitable for industrial production and promotion.
Smart Images

Figure CN119833657A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells and relates to a nitrogen-sulfur co-doped carbon material and a preparation method and application thereof. Background Art
[0002] Carbon materials have a wide range of sources and rich properties, and have been widely used in various fields. In the field of fuel cell electrochemistry, carbon materials are used as important precious metal carriers in electrocatalysts due to their excellent conductivity and rich pore structure. They can not only improve the activity of catalysts, but also greatly reduce the use of precious metals (such as platinum).
[0003] Currently, one of the commonly used catalysts in fuel cells is the platinum-carbon catalyst. Existing platinum-carbon catalysts generally use commercial carbon materials, such as conductive carbon black, which is considered to be a very good catalyst carrier material. However, the platinum-carbon catalyst prepared using the above-mentioned carrier has the problem of poor stability. This results in the oxygen reduction electrocatalytic stability of the existing platinum-carbon catalyst not reaching the optimal level and still cannot meet the large-scale commercial application needs of fuel cells.
[0004] Therefore, some researchers have modified carbon materials to improve performance. Patent CN114105122A discloses a method for preparing sulfur-doped carbon materials and their application as electrode catalyst carriers in electrochemistry; Patent CN114899437A invented a method for preparing nitrogen-doped mesoporous carbon-supported Pt fuel cell cathode catalysts. The nitrogen-doped mesoporous carbon-supported Pt fuel cell cathode catalyst prepared by loading Pt with this material can improve the stability of electrocatalytic oxygen reduction. However, using the above methods, it is difficult to ensure both the stability of the pore structure of the carbon carrier and the stability of the catalyst performance.
[0005] Therefore, there is an urgent need to modify the carbon material carrier to improve the stability of the corresponding platinum-carbon catalyst while ensuring the stability of the pore structure of the carbon carrier. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a nitrogen-sulfur co-doped carbon material and a preparation method and application thereof. The present invention performs nitrogen-sulfur diatomic doping on a carbon precursor, which not only does not destroy the pore structure of the carbon precursor, but also reasonably regulates the doping content, can introduce more active sites and defects, and can change the electronic structure of the carbon precursor, strengthen the interaction between the metal and the support, and thus improve the oxygen reduction reaction (ORR) activity and stability of the platinum-carbon catalyst.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a nitrogen-sulfur co-doped carbon material, the preparation method comprising:
[0009] (1) mixing a carbon precursor having a porous structure, a nitrogen source, a sulfur source and a dispersing solvent, drying and then heat treating to obtain a composite precursor, wherein the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is (3-15):1 (for example, it can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1, etc.);
[0010] (2) Acid washing the composite precursor described in step (1) to obtain the nitrogen-sulfur co-doped carbon material.
[0011] The present invention provides a method for preparing a nitrogen-sulfur co-doped carbon material, and a carbon precursor with a pore structure is doped with nitrogen-sulfur diatoms, not only without destroying the pore structure of the carbon precursor, but also rationally regulating the content of doping, and limiting the ratio of the carbon precursor mass to the sum of the mass of the nitrogen source and the sulfur source to (3-15): 1; On the basis that the carbon precursor can maintain the pore structure, the preparation method of the present invention is adopted, and less nitrogen source and sulfur source can be used to achieve high doping of nitrogen-sulfur diatoms, improve the utilization rate of the doping source, so that the final carbon material has a high doping atom content, more active sites and defects can be introduced, and the electronic structure of the carbon precursor can be changed at the same time, and the nitrogen-sulfur diatoms can also anchor platinum atoms, strengthen the interaction between metal and carrier, and then can improve the ORR reaction activity and stability of platinum-carbon catalyst. The preparation method of the present invention is simple, the synthesis process is controllable, the batch consistency is high, and the expansibility is strong, and industrialized production promotion can be realized.
[0012] In the present invention, if the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is too high, that is, the nitrogen source and the sulfur source are less, the nitrogen and sulfur content in the carbon material will be low, and the interaction between the platinum particles and the carrier cannot be well modified during the preparation of the platinum-carbon catalyst, and it will be difficult to improve the oxygen reduction catalytic activity; if the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is too low, that is, the nitrogen source and the sulfur source are more, resulting in too high a nitrogen and sulfur content in the carbon material, and the nitrogen and sulfur elements are unevenly distributed and unstable after being added, and the pore structure of the original carbon carrier is seriously blocked, which is not conducive to improving the catalyst activity.
[0013] Preferably, the carbon precursor in step (1) adopts a mature mass-produced commercial carbon carrier, which has good conductivity, high purity, uniform particle size, and high specific surface area.
[0014] Preferably, the carbon precursor in step (1) includes at least one of XC-72, XC-72R, EC-300J and EC-600JD.
[0015] In the present invention, the preferred carbon precursor has a multi-level pore structure.
[0016] Preferably, the particle size D50 of the carbon precursor in step (1) is 30 to 70 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 60 nm, 65 nm or 70 nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the specific surface area of the carbon precursor in step (1) is 180 to 1500 m 2 / g, for example, it can be 180m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g、500m 2 / g、700m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g or 1500m 2 / g, etc.
[0018] Preferably, the nitrogen source in step (1) comprises at least one of L-cysteine, methionine, thiourea and thioacetamide.
[0019] Preferably, the sulfur source in step (1) comprises at least one of L-cysteine, methionine, thiourea and thioacetamide.
[0020] In the present invention, the nitrogen source and the sulfur source are preferably organic substances containing both nitrogen and sulfur elements, which can achieve the simultaneous incorporation of nitrogen and sulfur elements without destroying the multi-level pore structure of the carbon precursor.
[0021] Preferably, the nitrogen source and the sulfur source are of the same type.
[0022] In the present invention, nitrogen source and sulfur source of the same type are preferred, which allows nitrogen and sulfur diatomic doping to be achieved by adding one raw material (such as any one of L-cysteine, methionine, thiourea or thioacetamide), which can simplify the process and facilitate industrial application.
[0023] Preferably, the dispersion solvent in step (1) comprises at least one of water, ethanol and isopropanol.
[0024] Preferably, the mass volume ratio of the carbon precursor and the dispersion solvent is (5-30) mg:1mL, for example, it can be 5mg:1mL, 6mg:1mL, 8mg:1mL, 10mg:1mL, 12mg:1mL, 15mg:1mL, 20mg:1mL, 25mg:1mL or 30mg:1mL, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In the present invention, if the mass-to-volume ratio of the carbon precursor to the dispersing solvent is too high, the carbon precursor concentration will be unevenly incorporated, and even block agglomeration will occur, resulting in reduced catalyst stability; if the mass-to-volume ratio of the carbon precursor to the dispersing solvent is too low, it will take a long time to prepare the nitrogen-sulfur co-doped carbon material, and the preparation efficiency will be low.
[0026] Preferably, the mixing process in step (1) is accompanied by ultrasound.
[0027] Preferably, the drying temperature in step (1) is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, and the drying time is 6-24h, for example, 6h, 8h, 10h, 15h, 18h, 20h, 22h or 24h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the temperature of the heat treatment in step (1) is 500-1000°C, for example, it can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In the present invention, too high a heat treatment temperature will greatly destroy the original pore structure of the carbon precursor. The high temperature causes the pores to collapse and become blocked, so that the surface area of the carrier is greatly reduced, thereby causing the catalyst activity and stability to be greatly reduced; too low a heat treatment temperature will fail to promote the formation of covalent bonds such as NC and SC, resulting in a lower content of incorporated nitrogen and sulfur, thereby causing the catalyst activity and stability to be greatly reduced.
[0030] Preferably, the heating rate of the heat treatment in step (1) is 5 to 20°C / min, for example, 5°C / min, 10°C / min, 15°C / min, 17°C / min or 20°C / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the heat treatment time in step (1) is 1 to 6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the atmosphere of the heat treatment in step (1) is an inert atmosphere, and the inert gas in the inert atmosphere includes nitrogen and / or argon.
[0033] Preferably, the flow rate of the inert gas is 30 to 200cc / min, for example, it can be 30cc / min, 50cc / min, 80cc / min, 100cc / min, 120cc / min, 150cc / min, 170cc / min or 200cc / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the acid used for pickling in step (2) includes hydrochloric acid and sulfuric acid.
[0035] In the present invention, the purpose of acid washing is to wash away impurity components (such as transition metal elements such as Fe, Ni and Cr) in the composite precursor, which have a poisoning effect on the Pt-based catalyst.
[0036] Preferably, the concentration of the acid is 0.1-10 mol / L, for example, it can be 0.1 mol / L, 0.2 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the pickling process in step (2) is accompanied by ultrasound, and the ultrasound time is 0.5 to 6 hours, for example, it can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, in step (2), after the acid washing, the steps of washing, solid-liquid separation and vacuum drying are performed in sequence.
[0039] As a preferred technical solution of the present invention, the preparation method specifically comprises:
[0040] (I) mixing a carbon precursor having a porous structure, a nitrogen source, a sulfur source and a dispersing solvent, drying and heat treating the mixture at 500-1000° C. for 1-6 hours to obtain a composite precursor, wherein the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is (3-15):1, the nitrogen source and the sulfur source independently include at least one of L-cysteine, methionine, thiourea and thioacetamide, and the nitrogen source and the sulfur source are of the same material type;
[0041] (II) Immersing the composite precursor described in step (I) in acid and ultrasonically treating for 0.5 to 6 hours to obtain an acid-washed product, then washing the acid-washed product with water until it is neutral, filtering it, and vacuum drying the filtered product at 50 to 90°C (for example, 50°C, 60°C, 70°C, 80°C or 90°C, etc.) for 8 to 24 hours (for example, 8 hours, 10 hours, 15 hours, 20 hours or 24 hours, etc.) to obtain the nitrogen-sulfur co-doped carbon material.
[0042] In the present invention, the pickling product is washed to neutrality, and the neutrality satisfies the following conditions: the pH value of the filtrate after filtration is 6 to 7.5, or the conductivity of the filtrate after filtration is less than 10 μS / m; wherein the pH value may be, for example, 6, 6.2, 6.5, 7 or 7.5, and the conductivity may be, for example, 9 μS / m, 8 μS / m, 7 μS / m, 6 μS / m or 5 μS / m.
[0043] In a second aspect, the present invention provides a nitrogen-sulfur co-doped carbon material, wherein the nitrogen-sulfur co-doped carbon material is prepared by the preparation method described in the first aspect.
[0044] In a third aspect, the present invention provides a platinum-carbon catalyst, comprising the nitrogen-sulfur co-doped carbon material described in the second aspect, and platinum metal particles supported on the nitrogen-sulfur co-doped carbon material.
[0045] In a fourth aspect, the present invention provides a method for preparing the platinum-carbon catalyst according to the third aspect, the preparation method comprising: (i) mixing a nitrogen-sulfur co-doped carbon material, a platinum source and a solvent, then heating the obtained mixture to a viscous state, and then freeze-drying the viscous mixture to obtain a freeze-dried product;
[0046] (ii) heat-treating the freeze-dried product of step (i) to obtain the platinum-carbon catalyst.
[0047] Preferably, the platinum source in step (i) comprises chloroplatinic acid.
[0048] Preferably, the mass ratio of the nitrogen-sulfur co-doped carbon material and the Pt element in the platinum source in step (i) is (3-9):(1-7), wherein the selection range of the nitrogen-sulfur co-doped carbon material (3-9) can be, for example, 3, 4, 5, 6, 7, 8 or 9, and the selection range of the Pt element in the platinum source (1-7) can be, for example, 1, 2, 3, 4, 5, 6 or 7, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0049] Preferably, the solvent in step (i) comprises water and ethanol.
[0050] Preferably, the heating temperature in step (i) is 50-80°C, for example, 50°C, 55°C, 60°C, 70°C, 75°C or 80°C, etc., and the heating process is accompanied by stirring, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the freeze-drying temperature in step (i) is -80 to -40°C, for example, -80°C, -70°C, -65°C, -60°C, -55°C, -50°C or -40°C, and the freeze-drying time is 12 to 48h, for example, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 20h, 25h, 30h, 35h, 40h or 48h, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0052] Preferably, the temperature of the heat treatment in step (ii) is 140-300°C, for example, it can be 140°C, 150°C, 180°C, 200°C, 220°C, 250°C, 270°C or 300°C, and the time of the heat treatment is 2-5h, for example, it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0053] Preferably, the atmosphere of the heat treatment in step (ii) is a reducing atmosphere, and the gases in the reducing atmosphere include hydrogen and argon.
[0054] Preferably, based on the total volume of the gas in the reducing atmosphere as 100%, the volume fraction of the hydrogen is 3-15%, for example, it can be 3%, 4%, 5%, 8%, 10%, 12% or 15%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In a fifth aspect, the present invention provides a fuel cell, comprising the platinum-carbon catalyst described in the third aspect.
[0056] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The present invention provides a method for preparing a nitrogen-sulfur co-doped carbon material, in which a carbon precursor having a pore structure is doped with nitrogen and sulfur diatoms, not only without destroying the pore structure of the carbon precursor, but also by reasonably regulating the doping content, and limiting the ratio of the mass of the carbon precursor to the sum of the mass of the nitrogen source and the sulfur source to (3-15):1; on the basis that the carbon precursor can maintain the pore structure, the preparation method of the present invention can use less nitrogen source and sulfur source to achieve high doping of nitrogen and sulfur diatoms, improve the utilization rate of the doping source, so that the final carbon material has a high doping atom content, can introduce more active sites and defects, and at the same time change the electronic structure of the carbon precursor, and the nitrogen and sulfur diatoms can also anchor platinum atoms, strengthen the interaction between the metal and the carrier, and thus improve the ORR reaction activity and stability of the platinum-carbon catalyst.
[0059] (2) The preparation method of the present invention is simple, the synthesis process is controllable, the batch consistency is high, and the scalability is strong, and industrial production and promotion can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is a TEM test image of the platinum-carbon catalyst provided in Application Example 1 of the present invention.
[0061] Figure 2 This is a comparison chart of the initial electrochemical activity tests of the platinum-carbon catalyst provided in Application Example 1 of the present invention and the commercial platinum-carbon catalyst provided in Comparative Application Example 7.
[0062] Figure 3 This is a test diagram of the electrochemical stability of the platinum-carbon catalyst provided in Application Example 1 of the present invention. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0064] Example 1
[0065] This embodiment provides a method for preparing a nitrogen-sulfur co-doped carbon material, comprising:
[0066] (1) 20 mL of ultrapure water was transferred into a 50 mL beaker, and then 400 mg of EC-600JD and 50 mg of methionine were weighed and dispersed in the ultrapure water. After being uniformly mixed by ultrasonication for 30 min, the mixture was transferred to a 60 ° C forced air drying oven and dried for 12 h. After the solvent was evaporated, a composite carbon material A1 was obtained, wherein the particle size D50 of EC-600JD was 50 nm and the specific surface area was 1300 m 2 / g;
[0067] (2) The obtained composite carbon material A1 was transferred to a magnetic boat and placed in a high-temperature tube furnace, nitrogen was introduced, and the gas flow rate was set to 100 cc / min, and then a heating program was set to start heating, from room temperature to 800°C at a heating rate of 10°C / min and kept at this temperature for 3 h, and then naturally cooled to room temperature and taken out to obtain composite carbon material A2;
[0068] (3) The obtained composite carbon material A2 is added to a 1 mol / L hydrochloric acid solution and ultrasonicated for 0.5 h, then filtered to obtain an acid-washed product, which is washed with ultrapure water for multiple times and filtered until it is neutral. At this time, the filtrate conductivity is less than 10 μS / m. Finally, the filter cake is placed in a vacuum drying oven at 60°C and dried for 16 h to obtain a nitrogen-sulfur co-doped carbon material.
[0069] Example 2
[0070] The difference between this embodiment and embodiment 1 is that the methionine in step (1) is replaced by L-cysteine.
[0071] The rest of the preparation methods and parameters were the same as those in Example 1.
[0072] Example 3
[0073] This embodiment provides a method for preparing a nitrogen-sulfur co-doped carbon material, comprising:
[0074] (1) 20 mL of ultrapure water was transferred into a 50 mL beaker, and then 100 mg of XC-72 and 30 mg of thiourea were weighed and dispersed in the ultrapure water. After being uniformly mixed by ultrasonication for 30 min, the mixture was transferred to a 70 ° C forced air drying oven and dried for 12 h. After the solvent was evaporated, a composite carbon material A1 was obtained, wherein the particle size D50 of XC-72 was 50 nm and the specific surface area was 220 m 2 / g;
[0075] (2) The obtained composite carbon material A1 was transferred to a magnetic boat and placed in a high-temperature tube furnace, nitrogen was introduced, and the gas flow rate was set to 50 cc / min, and then a heating program was set to start heating from room temperature to 600°C at a heating rate of 10°C / min and kept at this temperature for 4 h. After naturally cooling to room temperature, it was taken out to obtain the composite carbon material A2;
[0076] (3) The obtained composite carbon material A2 was added to a 4 mol / L hydrochloric acid solution and ultrasonicated for 0.5 h, then filtered to obtain an acid-washed product, which was washed with ultrapure water for multiple times and filtered until it was neutral. At this time, the filtrate conductivity was less than 10 μS / m. Finally, the filter cake was placed in a vacuum drying oven at 60°C and dried for 16 h to obtain a nitrogen-sulfur co-doped carbon material.
[0077] Example 4
[0078] This embodiment provides a method for preparing a nitrogen-sulfur co-doped carbon material, comprising:
[0079] (1) 20 mL of ultrapure water was transferred into a 50 mL beaker, and then 600 mg of EC-300J, 20 mg of thiourea and 20 mg of methionine were weighed and dispersed in ultrapure water. After being uniformly mixed by ultrasonication for 30 min, the mixture was transferred to a 100 °C forced air drying oven and dried for 12 h. After the solvent was evaporated, a composite carbon material A1 was obtained, wherein the particle size D50 of EC-300J was 50 nm and the specific surface area was 810 m 2 / g;
[0080] (2) The obtained composite carbon material A1 was transferred to a magnetic boat and placed in a high-temperature tube furnace, argon gas was introduced, and the gas flow rate was set to 200 cc / min, and then a heating program was set to start heating from room temperature to 1000°C at a heating rate of 10°C / min and kept at this temperature for 5 h. After naturally cooling to room temperature, it was taken out to obtain the composite carbon material A2;
[0081] (3) The obtained composite carbon material A2 was added into a 6 mol / L hydrochloric acid solution and ultrasonicated for 1 h, and then filtered to obtain an acid-washed product. The product was washed with ultrapure water for multiple times and filtered until it was neutral. At this time, the conductivity of the filtrate was less than 10 μS / m. Finally, the filter cake was placed in a vacuum drying oven at 60°C and dried for 24 h to obtain a nitrogen-sulfur co-doped carbon material.
[0082] Example 5
[0083] The difference between this embodiment and embodiment 1 is that in step (1), the volume of ultrapure water is adjusted so that the mass volume ratio of EC-600JD to ultrapure water is 31 mg / mL.
[0084] The rest of the preparation methods and parameters were the same as those in Example 1.
[0085] Example 6
[0086] The difference between this embodiment and embodiment 1 is that in step (1), the volume of ultrapure water is adjusted so that the mass volume ratio of EC-600JD to ultrapure water is 4 mg / mL, thereby extending the drying time to 22 h.
[0087] The rest of the preparation methods and parameters were the same as those in Example 1.
[0088] Example 7
[0089] The difference between this embodiment and embodiment 1 is that the temperature rising program in step (2) is adjusted to: heating from room temperature to 1100° C. at a heating rate of 10° C. / min and keeping at this temperature for 3 h.
[0090] The rest of the preparation methods and parameters were the same as those in Example 1.
[0091] Example 8
[0092] The difference between this embodiment and embodiment 1 is that the temperature rising program in step (2) is adjusted to: heating from room temperature to 400° C. at a heating rate of 10° C. / min and keeping at this temperature for 7 h.
[0093] The rest of the preparation methods and parameters were the same as those in Example 1.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that in step (1), the mass ratio of EC-600JD to methionine is adjusted to 16:1.
[0096] The rest of the preparation methods and parameters were the same as those in Example 1.
[0097] Comparative Example 2
[0098] The difference between this comparative example and Example 1 is that in step (1), the mass ratio of EC-600JD to methionine is adjusted to 2:1.
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 1 is that step (3) is omitted, that is, steps such as pickling are not performed.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Comparative Example 4
[0104] The difference between this comparative example and Example 1 is that in step (1), methionine is replaced by melamine, that is, only nitrogen doping is performed.
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Comparative Example 5
[0107] The difference between this comparative example and Example 1 is that in step (1), methionine is replaced by thiophene, that is, only sulfur doping is performed.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Comparative Example 6
[0110] This comparative example provides a carbon material, which is the same EC-600JD as that in Example 1.
[0111] Application Example 1
[0112] This application example provides a method for preparing a platinum-carbon catalyst based on nitrogen-sulfur co-doped carbon material, specifically comprising:
[0113] Weigh 200 mg of the nitrogen-sulfur co-doped carbon material prepared in Example 1 and dissolve it in 15 mL of ultrapure water and 1 mL of ethanol mixed solution, then add 5.13 mL of 200 mM chloroplatinic acid solution, mix evenly by ultrasonication, and then transfer to a 70°C heating platform, evaporate the solvent while stirring magnetically until most of the liquid disappears and becomes viscous, then freeze-dry at -83°C for 24 h, and finally place the freeze-dried powder in a tubular furnace for heat treatment in a 5% hydrogen-argon mixture. The heat treatment atmosphere is 5%, the heat treatment temperature is 150°C, the time is 2 h, and after naturally cooling to room temperature, a platinum-carbon catalyst with a platinum content of 50% is obtained.
[0114] TEM image of platinum carbon catalyst Figure 1 As shown, it can be clearly seen from the figure that the platinum-carbon catalyst prepared based on nitrogen-sulfur co-doped carbon material has platinum particles distributed very evenly on the carrier, with very small particle size dispersion and an average particle size of 2.0 nm.
[0115] Application Example 2-8
[0116] The difference from Application Example 1 is that the nitrogen-sulfur co-doped carbon material prepared in Example 1 is replaced by the nitrogen-sulfur co-doped carbon materials prepared in Examples 2-8 respectively.
[0117] The rest of the preparation methods and parameters are consistent with those in Application Example 1.
[0118] Comparative Application Examples 1-6
[0119] The difference from Application Example 1 is that the nitrogen-sulfur co-doped carbon material prepared in Example 1 is replaced by the nitrogen-sulfur co-doped carbon materials prepared in Comparative Examples 1-6 respectively.
[0120] The rest of the preparation methods and parameters are consistent with those in Application Example 1.
[0121] Comparative Application Example 7
[0122] This comparative application example provides a commercial platinum-carbon catalyst, whose model is TEC10E50E.
[0123] Comparative Application Example 8
[0124] This comparative application example provides a method for preparing a platinum-carbon catalyst, which specifically includes:
[0125] 50 mg of methionine and 5.13 mL of 200 mM chloroplatinic acid solution were dispersed in a mixed solution of 15 mL of ultrapure water and 1 mL of ethanol, and then 200 mg of EC-600JD was added and ultrasonically mixed. The obtained solution was then subjected to rotary evaporation to remove the solvent and naturally dried overnight. The dried sample was ground into powder, heated to 900 ° C at a rate of 5 ° C / min in a nitrogen atmosphere, kept warm for 2 hours, and then naturally cooled to room temperature. The annealed sample was acid-washed in a 0.5 M H2SO4 solution, filtered, and naturally dried overnight. The dried product was ground into powder and subjected to a second heat treatment. The conditions and parameters were exactly the same as those for the first heat treatment. After naturally cooling to room temperature, a platinum-carbon catalyst was obtained.
[0126] Performance Testing
[0127] The platinum-carbon catalysts provided in the above application examples and comparative application examples are tested, specifically including:
[0128] (1) Slurry preparation: 2 mL of ultrapure water, 2 mL of isopropanol, and 50 μL of 5% Nafion solution were added to 4.0 mg of the catalyst in sequence and mixed; then ultrasonication was performed with an ultrasonic power of not less than 200 W for 30 min to make the slurry uniformly mixed. During the ultrasonication process, the water bath temperature should be kept below 20°C;
[0129] (2) Electrode preparation: The catalyst loading on the electrode surface is 50 μg / cm 2 , take an appropriate amount of the dispersed slurry and evenly drop it onto the smooth and clean surface of the disk electrode twice, and let it dry naturally and completely as the working electrode;
[0130] (3) Electrochemical test: The working electrode was placed in an electrolytic cell to form a three-electrode system, in which the reference electrode was a reversible hydrogen electrode (RHE), the counter electrode was a Pt sheet, and the electrolyte was a 0.1 M perchloric acid solution saturated with N2. The linear sweep voltammetry (LSV) curve was then tested. The catalyst was first activated at a scan rate of 200 mV / s until the hydrogen desorption peak area no longer increased. The initial LSV polarization curve was then recorded at a scan rate of 10 mV / s in the voltage range of 0.025 V to 1.2 V (relative to the RHE). Finally, the LSV polarization curve was recorded again according to the test conditions of the initial LSV curve after scanning 100 mV / s in the voltage range of 0.6 V to 1.0 V (relative to the RHE) for 10,000 cycles.
[0131] Figure 2 The initial LSV curves of the platinum-carbon catalyst provided in Application Example 1 of the present invention and the commercial platinum-carbon catalyst provided in Comparative Application Example 7 are shown. It can be seen from the figure that compared with the commercial platinum-carbon catalyst, the oxygen reduction plan curve has a higher half-wave potential, and the mass activity at 0.9V reaches 0.42A / mgPt, which is significantly higher than the commercial platinum-carbon catalyst of 0.19A / mgPt.
[0132] Figure 3 The initial LSV curve of the platinum-carbon catalyst provided in Application Example 1 of the present invention and the LSV curve after scanning 10,000 cycles are shown. It can be seen from the figure that after 10,000 cycles of stable testing, the polarization curve has almost no deviation, the mass activity loss is negligible, and the platinum-carbon catalyst exhibits excellent electrochemical stability.
[0133] From the initial LSV polarization curves of each application example and comparative application example and the LSV polarization curves after scanning 10,000 cycles, the mass activity of each catalyst at 0.9 V was calculated, and the initial mass activity and the mass activity after scanning 10,000 cycles were obtained respectively; and the decay rate was calculated = (initial mass activity - mass activity after scanning 10,000 cycles) / initial mass activity × 100%. The test results are shown in Table 1.
[0134] Table 1
[0135]
[0136]
[0137] analyze:
[0138] It can be seen from the results of Application Examples 1-4 that the nitrogen-sulfur co-doped carbon material prepared by the method of the present invention, when used as a carrier of a platinum-carbon catalyst, exhibits excellent ORR reaction activity and stability.
[0139] It can be seen from the results of Application Examples 1 and 5-6 that if the mass-to-volume ratio of the carbon precursor to ultrapure water is too high, the carbon precursor concentration will be too high and unevenly incorporated, and even block agglomeration will occur, resulting in reduced ORR stability of the catalyst; if the mass-to-volume ratio of the carbon precursor to ultrapure water is too low, it will take a long time to prepare the nitrogen-sulfur co-doped carbon material, which will consume about 10 hours more time, and the preparation efficiency will be low.
[0140] It can be seen from the results of Application Examples 1 and 7-8 that if the heat treatment temperature in step (2) is too high, the original pore structure of the carbon precursor will be greatly destroyed. The high temperature causes the pores to collapse and become blocked, so that the surface activeness of the carrier is greatly reduced, thereby causing the catalyst activity and stability to be greatly reduced; if the heat treatment temperature in step (2) is too low, it will not promote the formation of covalent bonds such as NC and SC, resulting in a lower content of nitrogen and sulfur incorporated, thereby causing the catalyst activity and stability to be greatly reduced.
[0141] It can be seen from the results of Application Example 1 and Comparative Application Examples 1-2 that if the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is too high, that is, the nitrogen source and the sulfur source are relatively small, the nitrogen and sulfur content in the carbon material will be low, and the interaction between the platinum particles and the carrier cannot be well modified during the preparation of the platinum-carbon catalyst, and it will be difficult to improve the oxygen reduction catalytic activity; if the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is too low, that is, the nitrogen source and the sulfur source are relatively large, resulting in too high a nitrogen and sulfur content in the carbon material, and the nitrogen and sulfur elements are unevenly distributed and unstable after addition, and the pore structure of the original carbon carrier is seriously blocked, which is not conducive to improving the catalyst activity.
[0142] It can be seen from the results of Application Example 1 and Comparative Application Example 3 that if acid washing and other steps are not performed, the nitrogen-sulfur co-doped carbon material has a high content of impurity components, which will poison the Pt-based catalyst and cause a decrease in catalyst activity.
[0143] From the results of Application Example 1 and Comparative Application Examples 4-6, it can be seen that if the carbon precursor is only doped with nitrogen or sulfur alone, the active sites provided by nitrogen or sulfur alone are insufficient to anchor the Pt nanoparticles, and thus cannot effectively improve the stability of the active agent of the platinum-carbon catalyst. If the carbon precursor is not doped, the effect is worse than that of nitrogen or sulfur doping alone.
[0144] It can be seen from the results of Application Example 1 and Comparative Application Example 7 that the activity and stability of the platinum-carbon catalyst prepared by the present invention are superior to those of commercial platinum-carbon catalysts.
[0145] It can be seen from the results of Application Example 1 and Comparative Application Example 8 that if a carbon precursor, a platinum source, a nitrogen source, and a sulfur source are directly mixed to prepare a platinum-carbon catalyst, the doping effect is similar to that of adding nitrogen or sulfur alone. The coupling effect introduced by nitrogen-sulfur co-doping in the present invention may further enhance the activity and stability of the catalyst.
[0146] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a nitrogen-sulfur co-doped carbon material, characterized in that: The preparation method comprises: (1) mixing a carbon precursor having a porous structure, a nitrogen source, a sulfur source and a dispersion solvent, drying and then heat-treating to obtain a composite precursor, wherein the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is (3-15):1; (2) Acid washing the composite precursor described in step (1) to obtain the nitrogen-sulfur co-doped carbon material.
2. The preparation method according to claim 1, characterized in that: The carbon precursor in step (1) includes at least one of XC-72, XC-72R, EC-300J and EC-600JD; Preferably, the particle size D50 of the carbon precursor in step (1) is 30 to 70 nm; Preferably, the specific surface area of the carbon precursor in step (1) is 180 to 1500 m 2 / g; Preferably, the nitrogen source in step (1) comprises at least one of L-cysteine, methionine, thiourea and thioacetamide; Preferably, the sulfur source in step (1) comprises at least one of L-cysteine, methionine, thiourea and thioacetamide; Preferably, the nitrogen source and the sulfur source are of the same type; Preferably, the dispersion solvent in step (1) comprises at least one of water, ethanol and isopropanol; Preferably, the mass volume ratio of the carbon precursor to the dispersion solvent is (5-30) mg:1 mL.
3. The preparation method according to claim 1 or 2, characterized in that: The mixing process in step (1) is accompanied by ultrasound; Preferably, the drying temperature in step (1) is 50 to 100° C., and the drying time is 6 to 24 hours; Preferably, the temperature of the heat treatment in step (1) is 500-1000°C; Preferably, the heating rate of the heat treatment in step (1) is 5 to 20°C / min; Preferably, the heat treatment time in step (1) is 1 to 6 hours; Preferably, the atmosphere of the heat treatment in step (1) is an inert atmosphere, and the inert gas in the inert atmosphere includes nitrogen and / or argon; Preferably, the flow rate of the inert gas is 30 to 200 cc / min.
4. The preparation method according to any one of claims 1 to 3, characterized in that The acid used in the pickling in step (2) includes hydrochloric acid; Preferably, the concentration of the acid is 0.1 to 10 mol / L; Preferably, the pickling process in step (2) is accompanied by ultrasound, and the ultrasound time is 0.5 to 6 hours; Preferably, in step (2), after the acid washing, the steps of washing, solid-liquid separation and vacuum drying are performed in sequence.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method specifically comprises: (I) mixing a carbon precursor having a porous structure, a nitrogen source, a sulfur source and a dispersing solvent, drying and heat treating the mixture at 500-1000° C. for 1-6 hours to obtain a composite precursor, wherein the ratio of the mass of the carbon precursor to the total mass of the nitrogen source and the sulfur source is (3-15):1, the nitrogen source and the sulfur source independently include at least one of L-cysteine, methionine, thiourea and thioacetamide, and the nitrogen source and the sulfur source are of the same material type; (II) Immersing the composite precursor described in step (I) in acid and ultrasonically treating it for 0.5 to 6 hours to obtain an acid-washed product, then washing the acid-washed product with water until it is neutral, filtering it, and vacuum drying the filtered product at 50 to 90° C. for 8 to 24 hours to obtain the nitrogen-sulfur co-doped carbon material.
6. A nitrogen-sulfur co-doped carbon material, characterized in that: The nitrogen-sulfur co-doped carbon material is prepared by the preparation method according to any one of claims 1-5.
7. A platinum-carbon catalyst, characterized in that The platinum-carbon catalyst comprises the nitrogen-sulfur co-doped carbon material according to claim 6, and platinum metal particles supported on the nitrogen-sulfur co-doped carbon material.
8. A method for preparing the platinum-carbon catalyst according to claim 7, characterized in that: The preparation method comprises: (i) mixing a nitrogen-sulfur co-doped carbon material, a platinum source and a solvent, then heating the obtained mixture to a viscous state, and then freeze-drying the viscous mixture to obtain a freeze-dried product; (ii) heat-treating the freeze-dried product of step (i) to obtain the platinum-carbon catalyst.
9. The preparation method according to claim 8, characterized in that: The platinum source in step (i) comprises chloroplatinic acid; Preferably, the mass ratio of the nitrogen-sulfur co-doped carbon material and the Pt element in the platinum source in step (i) is (3-9):(1-7); Preferably, the heating temperature in step (i) is 50-80° C., and the heating process is accompanied by stirring; Preferably, the freeze-drying temperature in step (i) is -80 to -40°C, and the freeze-drying time is 12 to 48 hours; Preferably, the temperature of the heat treatment in step (ii) is 140-300° C., and the time of the heat treatment is 2-5 h; Preferably, the atmosphere of the heat treatment in step (ii) is a reducing atmosphere, and the gases in the reducing atmosphere include hydrogen and argon; Preferably, based on the total volume of the gas in the reducing atmosphere being 100%, the volume fraction of the hydrogen is 3-15%.
10. A fuel cell, characterized in that: The fuel cell comprises the platinum-carbon catalyst according to claim 7.
Citation Information
Patent Citations
Sulfur-doped carbon material as well as preparation method and application thereof
CN114105122A